The evaluation of shear bond strength of denture teeth to CAD/CAM dentures acrylic after aging in gastric acid - Neslihan Güntekin; Burcu Kızılırmak (Heliyon)
The aim of this in vitro study is to compare the shear bond strengths of denture base resins obtained by different methods with different artificial teeth and to investigate their resistance to bonding by gastric acid in patients with gastroesophageal reflux disease. Samples were prepared using two different manufacturing methods for denture base resins (heat-polymerization and CAD/CAM) and three different types of artificial teeth (acrylic, Microfiller Reinforced Polymer Matrix Composite and CAD/CAM milled). CAD/CAM-milled denture base was combined with three different artificial teeth, while heat-polymerized base was combined with acrylic teeth. Each base-tooth combination was randomly divided into 2 subgroups (n = 14). One subgroup was immersed in artificial gastric acid and the other in artificial saliva solution. Shear bond strength testing was performed using a universal testing machine. The results obtained were analysed using two-way ANOVA and multiple comparisons were examined using Tukey's test. A significance level of p < 0.050 was used.The heat-polymerized acrylic base and acrylic teeth groups showed the highest shear bond strength (p < 0.001). There is no significant difference between the shear bond strengths of artificial gastric acid and artificial saliva groups (p = 0.152).CAD/CAM milled denture base resin bonded to different types of prefabricated teeth show similar shear bond strength. The bond strength of acrylic teeth bonded to a heat-polymerized acrylic base is higher. Gastric acid does not affect the shear bond strength.